An Innovative Approach to Deliver Student-Directed Livestream Simulations During a Pandemic. Issue 6 (November 2021) - Crews, Cynthia S.; Parker, Elizabeth; Taylor, Kelli
Abstract : Abstract: University and facility closures because of COVID-19 required nursing programs to develop innovative ways to ensure students met clinical hour requirements, standards, and expectations. One rural university utilized student-directed livestream virtual simulation sessions that included synchronous prebriefing, student-directed simulation activity, and immediate debriefing. Students were anonymously surveyed for feedback and evaluation of the activities. Students reported the sessions were helpful for learning and required use of prioritization, clinical judgment, and communication/collaboration skills. Other responses included communication issues, audiovisual issues, and low realism, which prompted future recommendations.